2012
DOI: 10.1371/journal.pone.0037290
|View full text |Cite
|
Sign up to set email alerts
|

The Sedative Effect of Non-Alcoholic Beer in Healthy Female Nurses

Abstract: IntroductionThe hop (Humulus lupulus L.), a component of beer, is a sedative plant whose pharmacological activity is principally due to its bitter resins, in particular to the α-acid degradation product 2-methyl-3-buten-2-ol. The mechanism of action of hop resin consists of raising the levels of the neurotransmitter γ-aminobutyric acid (GABA), an inhibitory neurotransmitter acting in the central nervous system (CNS).ObjectivesTo analyze the sedative effect of hops as a component of non-alcoholic beer on the sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 33 publications
0
32
0
6
Order By: Relevance
“…14,15 This has also been suggested in two studies by Franco et al which used non-alcoholic beer as a dietary source of hops over a 2-week period in 30 university students and 17 healthy female nurses, respectively. 33,34 Both these studies reported improvement in night sleep quality (e.g. reduced sleep latency), with the latter study suggesting that the effects on sleep quality were also reflected in decreased self-reported anxiety levels, as measured by the State-Trait Anxiety Inventory.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…14,15 This has also been suggested in two studies by Franco et al which used non-alcoholic beer as a dietary source of hops over a 2-week period in 30 university students and 17 healthy female nurses, respectively. 33,34 Both these studies reported improvement in night sleep quality (e.g. reduced sleep latency), with the latter study suggesting that the effects on sleep quality were also reflected in decreased self-reported anxiety levels, as measured by the State-Trait Anxiety Inventory.…”
Section: Discussionmentioning
confidence: 94%
“…reduced sleep latency), with the latter study suggesting that the effects on sleep quality were also reflected in decreased self-reported anxiety levels, as measured by the State-Trait Anxiety Inventory. 34 However, these two studies were not conducted in a blinded manner, lacked a placebo-controlled arm and had a non-standardized source of hops, thus limiting the interpretation and implications of the reported findings, particularly regarding the hops effects on anxiety levels through improved sleep quality. In order to explore this hypothesis, welldesigned, placebo-controlled studies with subjective and objective measures of sleep quality, quantity and architecture will be required.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding to the decreased urinary levels of 5 HIAA after the consumption of non alcoholic beer to explain that it could be generated by the anxiolytic effect of hops [6][7][8] and lysine [18], it has been irrefut ably proved by the sedative effect of non alcoholic beer on a stressed population [20,24,25], because abnormal urinary levels of 5 HIAA have been associ ated to generalized anxiety disorder (GAD) [26,27] and the severity of the Hamilton Anxiety Rating Scale [28]. In particular, increased 5 HIAA levels were cor related with the Hamilton somatic subscale (items 7 to 13) with items related to somatic signs of anxiety: tension, intellectual difficulties, somatic muscular symptoms, somatic sensory symptoms, and genitouri nary symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In addi tion to the non alcoholic beer consumption in people with sleep problems, the sedative action associated with the components of hops and the amino acid lysine has been used to correct temporary sleep latency Effect of Non Alcohol Beer on Anxiety: Relationship of 5 HIAA 1 and sleep fragmentation disorders in human popula tions [20].…”
Section: Introductionmentioning
confidence: 99%
“…36 Ingestion of 333 ml nonalcoholic beer (containing around 1 g of hops) at dinnertime, compared to no beer, reduced sleep latency and improved sleep quality in healthy nurses doing shift work in one small trial. 37 The compounds responsible for hops effects on sleep have not been determined. One study in mice suggested that hops acted in part by activating melatonin receptors.…”
Section: Moderate Potency Hypnotic Herbsmentioning
confidence: 99%